2013
DOI: 10.3109/19396368.2012.745035
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs6166 polymorphism with FSH receptor transcript variants and steroid production in human granulosa cell cultures

Abstract: Follicle stimulating hormone receptor (FSHR) genetic variation at position 2039 A > G (rs6166, p.Asn680Ser) was repetitively shown to correspond to the measures of ovarian sensitivity and the outcomes of gonadotropin stimulation. However, to date, there has been no study revealing the mechanisms behind the associations observed. The aim of the present research was to investigate the relationship between rs6166 and mRNA expression of FSHR-dependent genes such as LHCGR, CYP19A1, and FSHR itself with particular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Allelic variants of FSHR determine different FSHR sensitivity's [20,24,26]. Because of that we expected to find that FSHR 's variants influence in the reproduction outcomes, in our results we observed that the number of MII oocytes and embryos are higher in Ala307Ala women.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Allelic variants of FSHR determine different FSHR sensitivity's [20,24,26]. Because of that we expected to find that FSHR 's variants influence in the reproduction outcomes, in our results we observed that the number of MII oocytes and embryos are higher in Ala307Ala women.…”
Section: Discussionsupporting
confidence: 70%
“…Perez Mayorga et al [20] was the first group that observed differences in Asn680Ser genotypes with dose of rFSH in COH. Other groups observed that the FSHR variants influence the basal FSH and estradiol levels with conflicting results [23,24,25,26,27], for this reason, the FSHR gene and others gene variations may play a role in modulating receptor sensitivity and intracellular second messenger cascades to exogenous hCG and other gonadotrophins [24,28], thus the FSHR SNPs may cause changes in the phosphorylation and glycosylation molecular mechanisms [29,30]. …”
Section: Introductionmentioning
confidence: 99%
“…The level of FSHR expression at transcript and protein levels was significantly reduced in women with AA genotype when compared with GG genotype Desai et al (2011) R242 S S Desai and others stimulation did not differ significantly between the three genotypes, suggesting that the probable contribution of polymorphism at position 680 needs further investigation in long-term GC culture system (Nordhoff et al 2011, Zalewski et al 2013. The level of FSHR expression also has an impact on the FSH action.…”
Section: Wunschmentioning
confidence: 97%
“…hGLC homozygous for each FSHR haplotype responded identically in terms of cAMP, progesterone and estradiol (E 2 ) production, measured at saturation (31). Another experiment suggested that hGLC homozygous for Asn at amino acid position 680 only 'tended' toward higher FSHinduced FSHR expression, whereas the expression of other well-known FSHR-dependent genes, such as LHCGR and CYP19A1, was not affected (32). We recently have analyzed the effects of FSHR exon 10 SNPs in vitro more in depth, looking at the kinetics of response and at different signal transduction pathways.…”
Section: Fshrmentioning
confidence: 99%